Education and science: current trends - Tiurin S. S., Lastkov D. O., Klimenko A. I., Mikhailova T. V., Shchedrina E. V., Sorokoumova G. V., Biisova G. I., Zaborovskaia I. M., Rezhapova I. M., Zabrodin A. V., Rekova V. S., Burukina O. A., Drachuk S. V., Barashkina S. B. (Education and science: current trends, 2018)
in the article the signs of world VUCA, skills necessary to the modern man, differences of soft skills from hard skills and, groups of soft skills are examined. The special attention is spared to the psychological training as method of necessary skills development, the research results of the psychological training influence on the dynamics of personality potentials development of freshmen are analyzed.
Keywords: личностный потенциал; исследование; мотивационно-ценностный компонент; research; SPOD мир; VUCA мир; обучение всю жизнь; гибкие навыки; твердые навыки; психологический тренинг; коммуникативный компонент; способность к прогнозированию социальной ситуации взаимодействия; SPOD world; VUCA world; life-long learning; soft skills; hard skills; psychological training; personality potential; motivational-valued component; communicative component; capacity for prognostication of social situation of cooperation